Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.paid.2020.110066
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness around the world: Age, gender, and cultural differences in loneliness

Abstract: The BBC Loneliness Experiment provided a unique opportunity to examine differences in the experience of lonelines across cultures, age, and gender, and the interaction between these factors. Using those data, we analysed the frequency of loneliness reported by 46,054 participants aged 16–99 years, living across 237 countries, islands, and territories, representing the full range of individualism-collectivism cultures, as defined by Hofstede (1997). Findings showed that loneliness increased with individualism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
328
3
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(415 citation statements)
references
References 35 publications
(30 reference statements)
23
328
3
10
Order By: Relevance
“…In a large scale study comprising 35,712 UK adults, younger adults were found particularly at risk of experiencing severe loneliness during the pandemic in comparison to the older age group (Bu et al, 2020). This result also lends support to earlier studies, which reported younger people to be signi cantly lonelier than older respondents (Barreto et al, 2020;Child & Lawton, 2019). A few possible explanations are offered here.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In a large scale study comprising 35,712 UK adults, younger adults were found particularly at risk of experiencing severe loneliness during the pandemic in comparison to the older age group (Bu et al, 2020). This result also lends support to earlier studies, which reported younger people to be signi cantly lonelier than older respondents (Barreto et al, 2020;Child & Lawton, 2019). A few possible explanations are offered here.…”
Section: Discussionsupporting
confidence: 83%
“…With regards to gender, the results of our study showed higher levels of social loneliness among female students when compared to their male counterparts. An increased social loneliness score in female students may be explained by the fact that women, compared to men, value participation in social activities more highly, prefer greater interpersonal connectedness, and are more sensitive to the interpersonal context (Barreto et al, 2020, thus making them more vulnerable to social loneliness during a mandatory lockdown where social contact with peers is limited. This result corroborates previous studies, which identi ed female young adults to be particularly more at risk of experiencing social loneliness than male young adults (Bu et al, 2020; Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the high expectations of strong ties are not met, it can increase loneliness. A study on this topic reveals that people in individualist (against collectivist) countries experience more loneliness 14 . In Turkey, as in the countries of the world, elderly population is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…According to a novel, worldwide study on the role of age, gender and cultural differences in loneliness of adults (conducted on N = 46,054 participants; Barreto et al, 2020), younger people, men and people in individualistic cultures report more loneliness than older people, women and people in collectivist cultures, respectively. These results suggest that age, gender and information about the culture of origin of participants (in the case of intercultural studies) need to be included as potential contributors to feelings of loneliness.…”
Section: Introductionmentioning
confidence: 99%